Encontros com um Brasil afro-pindorâmico : processo formativo de pesquisa contra colonial em terras indígenas no Espírito Santo - Leal, Aida Brandão (2019)
This dissertation is the result of a study carried out within the scope of the research "Traditional Indigenous Knowledge and Subjectivity Production: Memory and Health Policies", funded by CAPES, which involved research work in the indigenous villages of the state of Espírito Santo, with a greater emphasis on Tupinikim people. Through this field of research, the study deals with problematizations around Colonialist practices that affect in the processes of knowledge production, and pursues affirmations of other epistemic bases directed to the strengthening of the indigenous peoples and more aligned with their way of living. Thus, this work establishes as a formative process of research in a decolonization theory approach, nourished by meetings with the Tupinikim indigenous peoples and literatures of indigenous authors, with the purpose of fomenting greater engagement and agreement with the epistemologies that form the knowledges and ways of life of traditional peoples. This research goes into the history of the state of Espírito Santo that leads out to its process of social and historical formation constituted by the indigenous peoples, its nearforgotten and lessened memories and histories in the scope of their own history and State history and public policies built in its territory. The research points out to the importance of the development of the customs that are forged among indigenous peoples, sustained by the bond of belonging to the earth, generating relations of interaction, interdependence, coexistence between human beings and nonhumans. From these relations, it was found through research that the processes of transmission of traditional knowledge become inseparable between nature and cultural production. The research among indigenous peoples in decolonization theoretical approach points also to the challenge of inhabiting border territories in different ways of life and knowledge, which therefore requires openness to dialogue and a trans-specific Ethos.